Nauczanie Kościoła o wolności religijnej – zerwanie czy ciągłość tradycji? - Chaberek, Michał (Collectanea Theologica, 2016)
This paper elaborates upon the Catholic Church’s teachings on religious freedom in the period from The French Revolution to The Second Vatican Council. Based on quotations from the original documents, the author presents the evolution of the Church’s position that switched from the initial rejection to the final acceptance of the religious freedom over past two centuries. The fact of this dramatic change begs the question about the continuity of tradition and credibility of the contemporary stance of the Church. Based on the document by the International Theological Commission, “Memory and Reconciliation: The Church and the Faults of the Past”, as well as the teaching of Pope Benedict XVI, the author demonstrates that – in contrast to some contemporary interpretations – the hermeneutics of continuity is possible regarding Church’s teaching on religious freedom.